Investigating the potential role of corporate social responsibility (CSR), in management of HIV/AIDS at work place : a case study of garment industries in Thetsane Maseru - Gitari, Flora K. (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2007.